Evaluasi Kualitas Tanah dan Arahan Pengelolaannya pada Kebun Stroberi di Desa Pancasari Kecamatan Sukasada - Masana Frininta Sembiring; I Dewa Made Arthagama; I Wayan Narka (Fakultas Pertanian, Universitas Udayana, 2022)
This study aims to determine the status of soil quality, limiting factors, and provide direction for land management, as well as make a map of the status of soil quality on stroberi land in Pancasari Village. The methods used in this research are field survey methods, laboratory analysis, and soil quality determination. Soil samples were taken by the purposive sampling technique on each homogeneous land unit. Determination of SLH was done by overlaying soil type maps, slope maps, and stroberi land used maps in Pancasari Village. Soil quality indicators measured as minimum data set (MDS): soil texture, volume weight, porosity, C- Organic, pH, Cation Exchange Capacity (CEC), Base Saturation (BS), nutrients (N, P, and K), and C-biomass. The results showed that the soil quality at the research site was moderate in SLH 1 (Buyan Hamlet), while the good soil quality was found in SLH 2 (Dusun Peken), SLH 3 (Dasong Hamlet, Buyan Hamlet), SLH 4 (Dasong Hamlet, Buyan Hamlet), SLH 5 (Dusun Peken, Dusun Buyan) and SLH 6 (Dusun Dasong). The limiting factors for soil quality in the research site were nutrients BS. Based on the results of the study, it can be suggested that the directions for soil management at the research site, namely by adding organic matter.